Estudo de processos tecnológicos para a obtenção de produtos derivados da castanha-do-Brasil (Bertholletia Excelsa, H.B.K.) - Souza, Maria Luzenira de (1984)
In order to accomplish the present work, the raw material chosen was Brasil nut (Bertholleetia excelsa,H.B.R.) "in natura", from Belém, in the state of Para, harvested in 1984. Studies were conducted aiming to obtain micro-wave roasted and salted nuts, flour and milk, with and without the addition of chemical preservatives. These products were aúequated stored during 120 days for a study of shelf life. [...]